Local content and sustainable development in global energy markets / edited by Damilola S. Olawuyi, Hamad Bin Khalifa University. - Olawuyi, Damilola S. (Damilola Sunday), 1983- (Treaty implementation for sustainable development., 2021)
Local Content and Sustainable Development in Global Energy Markets analyses the topical and contentious issue of the critical intersections between local content requirements (LCRs) and the implementation of sustainable development treaties in global energy markets including Africa, Asia, Europe, North America, Latin America, South America, Australasia and the Middle East While LCRs generally aim to boost domestic value creation and economic growth, inappropriately designed LCRs could produce negative social, human rights and environmental outcomes, and a misalignment of a country's fiscal policies and global sustainable development goals. These unintended outcomes may ultimately serve as disincentive to foreign participation in a country's energy market. This book outlines the guiding principles of a sustainable and rights-based approach - focusing on transparency, accountability, gender justice and other human rights issues - to the design, application and implementation of LCRs in global energy markets to avoid misalignments.